The Education Myth : How Human Capital Trumped Social Democracy - Shelton, Jon, 1978- (Book collections on Project MUSE., 2023)
"Focusing on the era from the New Deal through the present, this book tells the story of how politicians, intellectuals, and other leaders in the United States emphasized investment in education through human capital at the expense of broader social democratic policies such as a jobs guarantee, union rights, and a robust social safety net"--